The Dynamics of Power, Violence, and Conflict of Nahdlatul Wathan (State Islamic University (UIN) of Sunan Ampel Surabaya, 2021)
The dynamics of Muslim communities of Nusa Tenggara Barat (NTB) in Lombok Island, have a profound emotional impact on the history of Nahdlatul Wathan (NW). It alters how social and religious systems are developed. Since 1953, NW has grown quickly to become the majority Islamic organization in Lombok due to the pioneers’ educational background, as well as their cultural and social capitals in the development of Islam. After the New Order, internal created two strongholds for conflict entities and reconciliation. Open violence has broken out in a number of Lombok locations due to conflicting forces. The integrated dualism of the organization's leadership has not been seen in the resolution of conflicts through practical politics. This article underlines how NW has evolved into one of the cases where division positively affects the growth of mass organizations.